Two-grade metabolic tumor tissue assessment using positron emission tomography in prediction of overall survival in glioblastoma patients - Lučić, Silvija; Djan, Igor; Vučaj-Ćirilović, Viktorija; Radovanović, Dragana; Kozarski, Dejan; Sen, Li; Ussov, Vladimir Y.; Lučić, Miloš A. (Vojnosanitetski pregled, 2022)
Background/Aim. Although considered rare, gliomas cause morbidity and mortality disproportionate to their incidence. The aim of the study was to determine whether pre and post-therapeutic metric values, derived from the FDG PET/CT maximal standardized uptake value (SUVmax) and calculated ratios between tumor and normal brain tissue, may provide a predictive/prognostic biomarker information in estimating overall survival of glioblastoma patients. Methods. In 26 out of 31 patients with glioblastoma treated with standard Stupp protocol after maximal safe reductive surgery, we performed a baseline 18F-FDG PET/CT examination before commencing combined and concomitant chemotherapy/radiotherapy (pre-therapy FDG PET/CT) and a second examination three months after the therapy completion (post-therapy FDG PET/CT). Two-graded SUVmax values and a calculated ratio of uptake in tumor-to-normal-tissue (T/N ratio) value, divided into two grades by the calculated cut-off value, were measured in all patients at both pre- and post-therapy FDG PET/CT studies. Data sets were statistically analyzed by the Kaplan-Meier survival test and Log-rank was calculated, with the level of confidence determined at p < 0.05. Results. Pre-therapy FDG PET/CT two-grade T/N ratio value and both pre- and post-therapy FDG PET/CT derived two-grade SUVmax values had a strong predictive impact on overall survival of glioblastoma patients. Conclusion. Based on two-grade SUVmax and T/N ratio values assessment, FDG PET/CT could provide valuable predictive survival information in glioblastoma patients and serve as a selection tool for identifying patients at higher risk from worse outcomes and shorter survival time.